HBT interferometry: historical perspective - Padula, Sandra S. [UNESP] (Sociedade Brasileira de Física, 2005)
I review the history of HBT interferometry, since its discovery in the mid 1950's, up to the recent developments and results from BNL/RHIC experiments. I focus the discussion on the contributions to the subject given by members of our Brazilian group.